PENGEMBANGAN DALAM BERWIRAUSAHA SABUN CAIR PENCUCI PIRING HANDMADE DI KELURAHAN SEMPAKATA, KECAMATAN MEDAN SELAYANG, KOTA MEDAN - Lasma Lenida Rosinta Sianipar; Hanna M Damanik; Dame Ria Rananta Saragi (Jurnal Abdimas Bina Bangsa, 2023)
Entrepreneurship can be interpreted as the process of the actions of an entrepreneur as someone who is always looking for something new and exploits these ideas into profitable opportunities by accepting risk and uncertainty with the company. Training activities were carried out at  the Sempakata Village Hall, Medan Selayang District, Medan City by inviting residents of the surrounding community by bringing materials and materials that will be used as training materials that can later be used as practice tools for the local community.  In addition, this dishwashing liquid soap can also be used and empowered among traditional markets as an enhancer of people's livelihoods in Sempakata Village, Medan Selayang District, Medan City